Integration of Cultural Digital form and Material Carrier form of Traditional Handicraft Intangible Cultural Heritage - Aljaberi S.M.; Al-Ogaili A.S. (American Scientific Publishing Group (ASPG), 2023)
Intangible cultural heritage is the continuous progress of human society. Intangible cultural heritage refers to various traditional cultural expressions that exist in intangible form and are closely related to the lives of the people and inherited from generation to generation. Intangible cultural heritage is a human-oriented living cultural heritage. It emphasizes human-centric skills, experience, and spirit, and is characterized by living changes. What stands out is the intangible attribute, and more emphasis on the quality that does not depend on the material form. The biggest feature of intangible cultural heritage is that it is not divorced from the special life and production methods of the nation, and it is the "living of the nation's personality and national aesthetic habits. "Appears. It exists on the basis of human beings, using voice, image and skills as means of expression, and passing from word to mouth as a cultural chain to continue. It is the most vulnerable part of "living" culture and its traditions. Therefore, for the process of inheriting intangible cultural heritage, the inheritance of people is particularly important. The traditional handicraft intangible cultural heritage is one of the best. However, with the rapid development of society, the living environment of intangible cultural heritage has changed, and the intangible cultural heritage of traditional handicraft industry is rapidly declining or even disappearing. In order to protect traditional handicraft intangible cultural heritage, this article studies the influence of the integration of traditional handcrafted intangible cultural heritage with the form of material carrier, reading and analyzing a large number of related documents using the literature survey method, and according to research needs, through the study of the content of the literature In summary, a questionnaire survey method was adopted to investigate traditional handicraft intangible cultural heritage visitors and inheritors. The results of the survey found that visitors satisfaction with the integration of digital forms and physical carrier forms of intangible cultural heritage projects was nearly 30% higher than that of unintegrated forms. Inheritors generally believe that integrated research has better publicity and education for traditional handicraft intangible heritage. The merged handmade intangible cultural heritage items are easy to store, retrieve and query, and at the same time help to preserve the related traditional handmade intangible cultural heritage items safely and for a long time, making the traditional handmade intangible cultural heritage items widely spread and shared around the world. 2021, American Scientific Publishing Group (ASPG). All rights reserved.